Influence of inorganic anions from atmospheric depositions on weathering steel corrosion and metal release. (10th March 2020) - Bernardi, Elena; Vassura, Ivano; Raffo, Simona; Nobili, Lara; Passarini, Fabrizio; de la Fuente, Daniel; Morcillo, Manuel
Highlights: Individual effects of Cl −, NO3 −, SO4 2− solutions on weathering steel were studied. NO3 − started to influence corrosion only by overcoming concentration/time thresholds. Cl − caused linear increase of mass loss and metal release with concentration/time. SO4 2− promoted passivation and suppresses metal release with concentration/time. Amount of released metals changed with metal, anion, concentration, time. Abstract: The individual effects of nitrate, chloride and sulphate on weathering steel appearance, patina composition, corrosion rate and metal release (Fe, Cr, Mn, Cu, Ni) were investigated by accelerated ageing with anion solutions at environmental concentrations. The anions influence the growth and evolution of corrosion products in the following order: SO4 2−  > Cl −  > NO3 − . Even though SO4 2− induces the highest kinetic in patina growth and metal release, it tends to passivate the alloy by suppressing both processes with increasing time and concentration. Cl −, conversely, does not induce any stabilization trend and seems to contribute more than the other anions to metal runoff.